Moisturizing soft all-cotton fabric and preparation method thereof
Through swelling and slapping treatment, combined with silane coupling agent and macromolecular hyaluronic acid, the problem of hair and moisturizing effects of cotton fabrics not lasting during finishing, achieving soft, fluffy and long-term moisturizing effects.
Patent Information
- Application Number
- CN202411430567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-25
AI Technical Summary
Existing cotton fabrics are prone to hair or down during the finishing process, resulting in a lack of smooth surface, stiff feel, and insufficient moisturizing effect, especially in dry climates.
Swelling and slapping treatment are adopted to reduce the adhesion between fibers by soaking in the moisturizer solution and combining ultrasound, the adhesion between fibers is increased, and the softness is improved. Then, a silane coupling agent and carboxy polyethylene glycol silane are used as the gel precursor solution, combined with macromolecular hyaluronic acid, to form a thin film structure, locking in moisturizing ingredients, and improving the washing resistance.
It realizes the long-term sustained moisturizing effect of all cotton fabrics, enhances the softness and fluffy feel of the fabric, and reduces the friction between the fabric's static electricity and fibers, and improves the washing resistance.
Smart Images

Figure BDA0005083543650000061 
Figure BDA0005083543650000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a moisturizing and soft all-cotton fabric and a preparation method thereof. Background Art
[0002] With the development of the times, people have higher and higher requirements for fabrics. Developing fabrics that can meet consumer needs plays an increasingly important role in fabric production. Cotton fabrics have good skin-friendliness and hygroscopicity, and have always been favored by people. When the fabric is in contact with human skin, the fabric needs to have a good touch, such as softness, fluffyness, skin-fitting, etc. Most of the pure cotton fabrics processed by the prior art lack smoothness and do not have a soft and elastic feel. This is mainly because during the finishing process of the pure cotton fabric, external forces (such as the physical action of the machine) will cause the surface of the fabric to produce hairiness or fluff, so the cloth surface lacks smoothness. Although some related finishing processes for mercerized fabrics have appeared in the prior art in order to obtain good smoothness of the fabric, although this type of finishing process can improve the surface smoothness of the fabric to a certain extent, the feel of the fabric will be obviously stiff, not soft enough and without elastic touch.
[0003] In addition, under normal circumstances, the stratum corneum of human skin has water absorption and barrier functions. At the same time, due to the covering effect of lipid substances secreted by sweat glands and sebaceous glands, the stratum corneum of human skin can maintain a certain water content. However, due to climate or skin damage, the stratum corneum will be dehydrated, resulting in the skin being in a dry and dehydrated state. This application is mainly aimed at the dry climate environment in northern winter, and provides a fabric that can be used for long-term sustained-release moisturizing. Although the existing patent technology mentions that the prepared fabric has a certain moisturizing effect, the moisturizing effect is not long-lasting, or the moisturizing effect of the fabric decreases significantly after multiple washings. Summary of the invention
[0004] The object of the present invention is to provide a moisturizing and soft cotton fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a moisturizing and soft cotton fabric, comprising the following preparation steps:
[0006] (1) Immerse the cotton fabric in a moisturizing agent solution of 8 to 12 times the mass of the cotton fabric, soak at 30°C for 20 minutes, add 60°C ethanol of half the volume of the moisturizing agent solution, seal and soak for 40 minutes, take out the fabric, dehydrate, and dry at 50°C for 30 minutes at a vacuum degree of 10 to 20 Pa to obtain the pretreated fabric;
[0007] (2) Silane coupling agent KH-540, carboxyl polyethylene glycol silane, methanol, and deionized water are mixed, stirred for 8 to 12 minutes, and then hyaluronic acid in an amount of 0.06 to 0.2 times the mass of the silane coupling agent KH-540 is added, and stirring is continued for 8 to 12 minutes to obtain a treatment solution;
[0008] (3) The treatment liquid and the pre-treated fabric are mixed in a weight ratio of 1:1 and placed in a beating device. After beating for 20 minutes under acid mist, the fabric is taken out, left to stand for 1 hour under acid mist, and then completely immersed in methanol for 24 hours. Dry at 100°C for 2 to 3 hours to obtain a moisturizing and soft cotton fabric.
[0009] Furthermore, the weight of the cotton fabric in step (1) is 120-160 g / m 2 .
[0010] Furthermore, the mass ratio of arginine, trehalose, sodium hypophosphite and deionized water in the moisturizing solution of step (1) is 10:10:5:100.
[0011] Furthermore, step (1) is performed entirely at an ultrasonic frequency of 25 to 35 kHz.
[0012] Furthermore, the molecular weight of the hyaluronic acid in step (2) is 6-10 million.
[0013] Furthermore, the molecular weight of the carboxyl polyethylene glycol silane in step (2) is 1000.
[0014] Furthermore, in step (2), the weight ratio of the silane coupling agent KH-540, carboxyl polyethylene glycol silane, methanol, and deionized water is 1:0.3-0.5:2-3:0.9-1.1.
[0015] Furthermore, the stirring speed in step (2) is 80 rpm.
[0016] Furthermore, the acid mist in step (3) is formed by an oxalic acid aqueous solution with a pH of 3 to 4 through pressurized air at a rate of 1 to 3 L / min and a temperature of 50°C.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] The present invention first performs a swelling treatment on the cotton fabric, and cooperates with ultrasound to reduce the cohesion between fibers, while fully expanding. In the later drying process, rapid volatilization is used to leave larger pores between fibers, thereby making the fabric more fluffy and improving the softness of the cotton fabric. At the same time, the gaps in the fibers provide adsorption sites for small molecule moisturizers. The -OH of the cotton fabric itself and the small molecule moisturizer are tightly cross-linked on the fibers through hydrogen bonds and chemical bonds, thereby maintaining the long-term moisturization of the fabric and promoting the small molecule moisturizer to penetrate into the skin. Then, silane coupling agent KH-540 and carboxyl polyethylene glycol silane are used as gel precursor liquid, and macromolecular hyaluronic acid is doped therein, and then the fabric is immersed in the gel precursor liquid and patted. While the fabric is fluffy, the precursor liquid can be driven to better infiltrate and bind to the surface of the fabric, thereby effectively reducing the use of the precursor liquid. The amount of silane is reduced, the consumption is relatively reduced, the waste water is reduced, and the chemicals in the precursor solution are used more effectively; in addition, during the beating process, the whole process is in an acidic environment, which promotes the hydrolysis of the silane coupling agent KH-540 and the carboxyl polyethylene glycol silane to form a gel coated on the fiber to form a film structure, thereby playing a smoothing effect, effectively reducing the static electricity of the fabric and the friction between the fibers, so that the fibers can be stretched and not easily bonded into a mass, thereby obtaining a softening effect. At the same time, the polysiloxane molecular chain segment further enhances the softening effect; and the carboxyl and amino groups on the side chains of the polysilane molecules improve the hydrophilicity of the gel, enhance the water-washing resistance, and can hydrogen bond with the macromolecular hyaluronic acid and the fabric, thereby locking the moisturizing components in the gel structure and on the fiber, which are not affected by water washing, and the present invention uses moisturizing components of different molecular weights to be used in combination, which can better and more lastingly maintain the moisturizing effect. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the moisturizing and soft cotton fabrics prepared in the following examples are as follows:
[0021] Moisturizing effect test: The fabrics of the embodiment and the comparative example were further processed into the same underwear and provided to 20 testers who had been trained in skin feel evaluation. The moisturizing effect was evaluated by the skin feeling of the clothes after the first and 100th washings. The test standard was evaluated on a scale of 1-10, and the average score of the 20 testers was taken for effect evaluation. Among them, 1-2 points indicated dissatisfaction, 3-4 points indicated relatively satisfied, 5-6 points indicated relatively satisfied, 7-8 points indicated satisfied, and 9-10 points indicated very satisfied.
[0022] Softness test: For each group of examples and comparative examples, 6 rectangular block samples of 6 cm × 10 cm were prepared for testing, of which the long sides of 3 samples were parallel to the longitudinal direction of the fabric, and the long sides of 3 samples were parallel to the transverse direction of the fabric. The samples were humidified for 24 hours under standard atmospheric conditions before testing, and there were no defects on the samples. The samples were tested for bending stiffness using the LLY-01 electronic stiffness tester produced by Laizhou Electronic Instrument Co., Ltd. The test result is the sum of the average value of the longitudinal test value and the average value of the transverse test value.
[0023] Example 1
[0024] (1) Set the weight to 120g / m 2 The cotton fabric is immersed in a moisturizing solution of 8 times the mass of the cotton fabric, and then soaked at 30°C for 20 minutes. Then, 60°C ethanol of half the volume of the moisturizing solution is added, and the fabric is sealed and soaked for 40 minutes. Then, the fabric is taken out, dehydrated, and dried at 50°C for 30 minutes at a vacuum degree of 10Pa to obtain the pretreated fabric; the mass ratio of arginine, trehalose, sodium hypophosphite and deionized water in the moisturizing solution is 10:10:5:100; the step (1) is performed at 25kHz throughout the process;
[0025] (2) Silane coupling agent KH-540, carboxyl polyethylene glycol silane with a molecular weight of 1000, methanol, and deionized water were mixed in a weight ratio of 1:0.3:2:0.9, stirred at 80 rpm for 8 minutes, and then hyaluronic acid with a weight of 0.06 times that of the silane coupling agent KH-540 was added, and stirring was continued for 8 minutes to obtain a treatment solution; the hyaluronic acid had a molecular weight of 6 million;
[0026] (3) The treatment liquid and the pretreated fabric are mixed in a weight ratio of 1:1 and placed in a beating device. After beating for 20 minutes under acid mist, the fabric is taken out, left to stand for 1 hour under acid mist, and then completely immersed in methanol for 24 hours, and dried at 100°C for 2 hours to obtain a moisturizing and soft cotton fabric; the acid mist is formed by an oxalic acid aqueous solution with a pH of 3 and pressurized air at a rate of 1 L / min and a temperature of 50°C.
[0027] Example 2
[0028] (1) Set the weight to 120g / m2 The cotton fabric is immersed in a moisturizing solution with a volume 10 times that of the cotton fabric, and then soaked at 30°C for 20 minutes. Then, 60°C ethanol with a volume half that of the moisturizing solution is added. After being sealed and soaked for 40 minutes, the fabric is taken out, dehydrated, and dried at 50°C for 30 minutes at a vacuum degree of 15 Pa to obtain the pretreated fabric. The mass ratio of arginine, trehalose, sodium hypophosphite, and deionized water in the moisturizing solution is 10:10:5:100. The step (1) is performed at 25kHz throughout.
[0029] (2) Silane coupling agent KH-540, carboxyl polyethylene glycol silane with a molecular weight of 1000, methanol, and deionized water were mixed in a weight ratio of 1:0.4:3:1, stirred at 80 rpm for 10 min, and then hyaluronic acid with a mass of 0.13 times that of the silane coupling agent KH-540 was added, and stirring was continued for 10 min to obtain a treatment solution; the hyaluronic acid had a molecular weight of 6 million;
[0030] (3) The treatment liquid and the pretreated fabric are mixed in a weight ratio of 1:1 and placed in a beating device. After beating for 20 minutes under acid mist, the fabric is taken out, left to stand for 1 hour under acid mist, and then completely immersed in methanol for 24 hours, and dried at 100°C for 2.5 hours to obtain a moisturizing and soft cotton fabric; the acid mist is formed by an oxalic acid aqueous solution with a pH of 3 and pressurized air at a rate of 2 L / min and a temperature of 50°C.
[0031] Example 3
[0032] (1) Set the weight to 120g / m 2 The cotton fabric is immersed in a moisturizing solution of 12 times the mass of the cotton fabric, and after soaking at 30°C for 20 minutes, 60°C ethanol with half the volume of the moisturizing solution is added, and the fabric is sealed and soaked for 40 minutes, and then the fabric is taken out, dehydrated, and dried at 50°C for 30 minutes at a vacuum degree of 20Pa to obtain the pretreated fabric; the mass ratio of arginine, trehalose, sodium hypophosphite and deionized water in the moisturizing solution is 10:10:5:100; the step (1) is performed at 25kHz throughout the process;
[0033] (2) Silane coupling agent KH-540, carboxyl polyethylene glycol silane with a molecular weight of 1000, methanol, and deionized water were mixed in a weight ratio of 1:0.5:3:1.1, stirred at 80 rpm for 8 to 12 minutes, and then hyaluronic acid with a weight of 0.2 times that of the silane coupling agent KH-540 was added, and stirring was continued for 12 minutes to obtain a treatment solution; the hyaluronic acid had a molecular weight of 6 million;
[0034] (3) The treatment liquid and the pretreated fabric are mixed in a weight ratio of 1:1 and placed in a beating device. After beating for 20 minutes under acid mist, the fabric is taken out, left to stand for 1 hour under acid mist, and then completely immersed in methanol for 24 hours, and dried at 100°C for 3 hours to obtain a moisturizing and soft cotton fabric; the acid mist is formed by an oxalic acid aqueous solution with a pH of 4 through pressurized air at a rate of 3 L / min and a temperature of 50°C.
[0035] Comparative Example 1
[0036] The difference between Comparative Example 1 and Example 2 is that step (1) is changed to: 2 The cotton fabric is immersed in a moisturizing solution with a mass 10 times that of the cotton fabric, and after soaking at 30°C for 20 minutes, the fabric is taken out, dehydrated, and dried at room temperature for 12 hours to obtain the pretreated fabric; the mass ratio of arginine, trehalose, sodium hypophosphite, and deionized water in the moisturizing solution is 10:10:5:100, and the step (1) is performed at 25kHz throughout the process; the remaining steps are the same as those in Example 2.
[0037] Comparative Example 2
[0038] The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: 2 The cotton fabric is immersed in a moisturizing solution with a volume 10 times that of the cotton fabric, and then soaked at 30°C for 20 minutes. Then, 60°C ethanol with a volume half that of the moisturizing solution is added. After being sealed and soaked for 40 minutes, the fabric is taken out, dehydrated, and dried at 50°C for 30 minutes at a vacuum degree of 15 Pa to obtain the pretreated fabric. The mass ratio of hyaluronic acid with a molecular weight of 6 million, sodium hypophosphite, and deionized water in the moisturizing solution is 10:5:100. The step (1) is performed at 25 kHz throughout the process. The remaining steps are the same as those in Example 2.
[0039] Comparative Example 3
[0040] The difference between Comparative Example 3 and Example 2 is that there is no step (1), and step (3) is changed to: mixing the treatment liquid with a gram weight of 120 g / m 2 The cotton fabrics are mixed in a weight ratio of 1:1 and placed in a beating device. After beating for 20 minutes under acid mist, the fabrics are taken out, left to stand for 1 hour under acid mist, and then completely immersed in methanol for 24 hours, and dried at 100°C for 2.5 hours to obtain moisturizing and soft cotton fabrics; the acid mist is formed by pressurized air with an oxalic acid aqueous solution with a pH of 3 at a rate of 2 L / min and a temperature of 50°C; the remaining steps are the same as those in Example 2.
[0041] Comparative Example 4
[0042] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: silane coupling agent KH-540, carboxyl polyethylene glycol silane with a molecular weight of 1000, methanol, and deionized water are mixed in a weight ratio of 1:0.4:3:1, and stirred at 80 rpm for 10 min to obtain a treated liquid; the remaining steps are the same as in Example 2.
[0043] Comparative Example 5
[0044] The difference between Comparative Example 5 and Example 2 lies in step (3). Step (3) is changed to: mixing the treatment liquid and the pretreated fabric in a weight ratio of 1:1, standing for 1 hour under acid mist, taking out the fabric, and then completely immersing it in methanol for 24 hours, and drying it at 100°C for 2.5 hours to obtain a moisturizing and soft cotton fabric; the acid mist is formed by pressurized air with an oxalic acid aqueous solution of pH 3 at a rate of 2L / min and a temperature of 50°C; the remaining steps are the same as Example 2.
[0045] Comparative Example 6
[0046] The difference between Comparative Example 6 and Example 2 is that step (3) is different. Step (3) is changed to: the treatment liquid and the pretreated fabric are mixed in a weight ratio of 1:1 and placed in a beating device. After beating for 20 minutes, it is completely immersed in methanol for 24 hours and dried at 100°C for 2.5 hours to obtain a moisturizing and soft cotton fabric; the remaining steps are the same as Example 2.
[0047] Comparative Example 7
[0048] The difference between Comparative Example 7 and Example 2 is that steps (2) and (3) are omitted, and the remaining steps are the same as those of Example 2.
[0049] Effect example
[0050] Table 1 below shows the performance analysis results of the moisturizing and soft cotton fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0051] Table 1
[0052]
[0053]
[0054] The present invention adopts hyaluronic acid of different molecular weights for use in combination, which can maintain the moisturizing effect better and more lastingly, and relies on silicone gel to lock the moisturizing ingredients so that they are not affected by water washing. The fabric is subjected to swelling treatment and patting treatment to reduce the cohesion between fibers and improve the softness of the cotton fabric. The silicone gel can smooth the fibers, effectively reduce the static electricity of the fabric and the friction between the fibers, so that the fibers can stretch and are not easily adhered to each other, thereby achieving a softening effect.
[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a moisturizing and soft cotton fabric, characterized in that: The method comprises the following preparation steps: (1) Immerse the cotton fabric in a moisturizing agent solution of 8 to 12 times the mass of the cotton fabric, soak at 30°C for 20 minutes, add 60°C ethanol of half the volume of the moisturizing agent solution, seal and soak for 40 minutes, take out the fabric, dehydrate, and dry at 50°C for 30 minutes at a vacuum degree of 10 to 20 Pa to obtain the pretreated fabric; (2) Silane coupling agent KH-540, carboxyl polyethylene glycol silane, methanol, and deionized water are mixed, stirred for 8 to 12 minutes, and then hyaluronic acid in an amount of 0.06 to 0.2 times the mass of the silane coupling agent KH-540 is added, and stirring is continued for 8 to 12 minutes to obtain a treatment solution; (3) The treatment liquid and the pre-treated fabric are mixed in a weight ratio of 1:1 and placed in a beating device. After beating for 20 minutes under acid mist, the fabric is taken out, left to stand for 1 hour under acid mist, and then completely immersed in methanol for 24 hours. Dry at 100°C for 2 to 3 hours to obtain a moisturizing and soft cotton fabric.
2. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: The weight of the cotton fabric in step (1) is 120-160 g / m 2 .
3. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: The mass ratio of arginine, trehalose, sodium hypophosphite and deionized water in the moisturizing solution of step (1) is 10:10:5:
100.
4. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: The entire step (1) is carried out at an ultrasonic frequency of 25 to 35 kHz.
5. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: The hyaluronic acid in step (2) has a molecular weight of 6-10 million.
6. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: The molecular weight of the carboxyl polyethylene glycol silane in step (2) is 1000.
7. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: In step (2), the weight ratio of the silane coupling agent KH-540, carboxyl polyethylene glycol silane, methanol and deionized water is 1:0.3-0.5:2-3:0.9-1.
1.
8. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: The stirring speed in step (2) is 80 rpm.
9. The method for preparing a moisturizing and soft cotton fabric according to claim 1, characterized in that: The acid mist in step (3) is formed by an oxalic acid aqueous solution with a pH of 3 to 4 through pressurized air at a rate of 1 to 3 L / min and a temperature of 50°C.